Molluscan Remains From Four Archeological Sites in Northeastern Ohio - James L. Murphy (Hello World!, 1971)
Partial excavation of four northern Ohio archeological sites assignable to the Whittlesey Focus of Greenman (1937) has yielded molluscan shell samples from both the Cuyahoga and Grand River drainages. The excavations were sponsored by the Cleveland Natural Science Museum, and reports on other aspects of the work have been published elsewhere (Murphy , 1971a, b).